IL-6 Promoter Hypomethylation Acts As a Diagnostic Biomarker in Hepatitis B Virus-Associated Hepatocellular Carcinoma - Yang, Jie-Ru; Wang, Ju; Li, Hai-Ming; Gao, Shuai; Fan, Yu-Chen; Wang, Kai (Frontiers in Oncology, 2022)
Background: New biomarkers are needed to detect hepatocellular carcinoma at an earlier stage and to individualize treatment strategies. IL-6 has been proven to be associated with liver cancer in numerous studies. Aim: To evaluate the value of the IL-6 promoter methylation level as a noninvasive biomarker for the diagnosis of liver cancer. Methods: A retrospective analysis of 165 patients with HBV-associated hepatocellular carcinoma (HCC), 198 patients with chronic hepatitis B (CHB) and 31 healthy controls were involved. The methylight was detected the methylation level of the IL-6 promoter in peripheral blood mononuclear cells (PBMCs), clinical and laboratory parameters were obtained. Results: IL-6 promoter methylation levels were significantly lower in patients with HCC (median 53.59%, interquartile range 52.01–54.75%) than in those with CHB (median 56.05%, interquartile range 54.65–57.67%; P<0.001). The level of IL-6 mRNA in patients with HCC (median 0.371, interquartile range 0.173-0.671) was significantly higher than that in patients with CHB (median 0.203, interquartile range 0.108-0.354; P<0.001) and HCs (median 0.189, interquartile range 0.140-0.262; P=0.001). Meanwhile, the PMR value of IL-6 was notably negatively correlated with the mRNA expression level (Spearman's R=-0.201, P<0.001). The IL-6 PMR value of HCC patients in age (Spearman's R=0.193，P=0.026) and TBIL (Spearman's R=0.186, P=0.032) were very weak correlated. At the same time, the level of IL-6 promoter methylation was also an independent factor in the development of liver cancer. When the IL-6 promoter methylation level was used to diagnose HCC, its detective value was superior to AFP [area under the receiver operating characteristic curve (AUC) 0.773 vs. 0.686, P=0.027]，And the combined use of AFP and IL-6 methylation level Conclusions：IL-6 promoter hypomethylation is present in hepatocellular carcinoma, and it may be used as a noninvasive biomarker to detect early liver cancer.